Importancia de la estimulación temprana y su incidencia en los estudiantes de preescolar con síndrome del autismo en las Escuelas Fiscales de Babahoyo, período lectivo 2022 - Valero Valle, Pamela Noemy (2022)
Autism spectrum disorder (ASD) is currently one of the developmental disorders with the highest prevalence rates. Its high figures, together with the difficulties for communication and social interaction, the repetitive and stereotyped patterns of behavior and the limited repertoire of interests that minors with ASD present, make it, in practice, one of the most complex issues for society and, consequently, for educational professionals. In this work, the main milestones regarding these issues are addressed, as well as the consideration of early care (TA) as a fundamental element to face this challenge. Indeed, the techniques of early detection and interdisciplinary intervention with the minor, the family and the environment, offered by TA, represent a strategy of recognized efficacy. However, the advances in research and the changes experienced in the conceptualization of the disorder, together with the impetus that the new TA paradigm implies, raise the need to advance knowledge about the challenges that remain unresolved in this field.